Perlindungan Hukum Bagi Artis atas Penggunaan Potret dalam Cover Novel Fanfiksi - Paramita Cahyaning Dewanti; Rahmadi Indra Tektona (Faculty of Law, Universitas Pattimura, 2021)
Intellectual Property Rights translated from Intellectual Property Right are the right to do something on the intellectual property which is regulated by applicable norms or laws. The purpose of this thesis research consists of general objectives and specific objectives, namely to find out and analyze the form of legal protection for Portraits, legal consequences, and efforts to resolve Portrait disputes. The research method includes the juridical - normative research type, while the research approach used is the statute approach. The result of this research is that portrait work is one of the copyrighted works protected by copyright law. which is contained in article 40 paragraph 1. This protection is given to the creator, namely the photographer and the copyright holder is the person photographed. This protection is given to motivate and encourage the creativity of creators who can create economic growth based on the scope of art, literature and science and provide an understanding to the public that portrait works are protected by law No. 28 of 2014 concerning copyright, where there is a prohibition for other people. use the copyright work arbitrarily without the permission of the creator or copyright holder. Acts of violating the copyright of Portrait's works that are used commercially without rights can be sued civil or criminal or can be done both, but if you want to do both, you must prioritize civil settlement then criminally. but the verdict of his civil case cannot waive his criminal sentence. Then to resolve the dispute, it can be done by litigation and also in non-litigation, namely dispute resolution by negotiation, mediation, and arbitration.